2005
DOI: 10.1002/ijc.21105
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen receptor α polymorphisms with breast cancer risk in older Caucasian women

Abstract: Estrogens exert their effect on the breast through the estrogen receptor. We prospectively investigated breast cancer risk associated with 2 polymorphic sites in the estrogen receptor alpha gene (ESR1). A total of 4,248 Caucasian women from the Study of Osteoporotic Fractures were genotyped for the 2401 T/C and 2354 A/G polymorphisms in ESR1. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the associations between genotypes and breast cancer. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Previous smaller studies 18 -21,23 and a recent large cohort study 24 (4248 women followed up for 12.4 years; 252 events) on the association between the ESR1 IVS1-397T/C polymorphism of the ESR1 and risk of breast cancer showed no association, whereas a Chinese case-control study of 1069 cases and 1166 controls, in accordance with our results, showed an increase in risk of breast cancer with age-adjusted odds ratios for IVS1-397T/C genotypes TT versus CC of 1.4 (95% CI, 1.1 to 1.8). 22 Furthermore, a combined odds ratio for 5 of the previous studies 17-20,22 was 1.23 (95% CI, 1.08 to 1.43) on risk of breast cancer for TT versus CC genotype of the ESR1 IVS1-397T/C polymorphism.…”
Section: Cancer Of Reproductive Organsmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous smaller studies 18 -21,23 and a recent large cohort study 24 (4248 women followed up for 12.4 years; 252 events) on the association between the ESR1 IVS1-397T/C polymorphism of the ESR1 and risk of breast cancer showed no association, whereas a Chinese case-control study of 1069 cases and 1166 controls, in accordance with our results, showed an increase in risk of breast cancer with age-adjusted odds ratios for IVS1-397T/C genotypes TT versus CC of 1.4 (95% CI, 1.1 to 1.8). 22 Furthermore, a combined odds ratio for 5 of the previous studies 17-20,22 was 1.23 (95% CI, 1.08 to 1.43) on risk of breast cancer for TT versus CC genotype of the ESR1 IVS1-397T/C polymorphism.…”
Section: Cancer Of Reproductive Organsmentioning
confidence: 87%
“…Postmenopausal women with ESR1 IVS1-397T/C CC versus TT genotype undergoing hormone replacement therapy (HRT) had an augmented response of high-density lipoprotein (HDL) cholesterol levels 3 and greater reductions in E-selectin, 2 both of which could influence risk of disease in estrogen-responsive organ systems. In addition, there have already been several studies of the ESR1 IVS1-397T/C polymorphism in relation to CVD, 4 -16 breast cancer, [17][18][19][20][21][22][23][24] endometrial cancer, 25,26 prostate cancer, [27][28][29][30][31] and hip fracture, 32,33 although the results have been conflicting. It is therefore biologically plausible that the ESR1 IVS1-397T/C polymorphism may modify the effect of endogenous estrogen on risk of CVD, cancer of reproductive organs, and osteoporotic fractures like hip fracture.…”
Section: Clinical Perspective P 871mentioning
confidence: 99%
“…Modugno et al 16 found a modest but nonsignificant decrease in breast cancer risk associated with 2 loci in ESR1 for a range of population subgroups defined by various life style factors in Caucasians (2354 A/G and -401 T/C). Gold et al 10 identified protective haplotypes (H4, H6, H13) in the ESR1 gene in a mixed population and one in particular (H6) when the European-American subset population was analyzed, while Hsiao et al, 11 found that the SNP S10S (rs2077647) was associated with reduced breast cancer risk in a Taiwanese population.…”
Section: Genotype Distributionmentioning
confidence: 99%
“…The three most widely studied polymorphisms of the ESR1, the PvuII 397T > C, the XbaI (351A > G) restriction fragment length polymorphisms, both located in intron 1, and the TA repeat within the promoter region of the gene, are in linkage disequilibrium [18,19]. These polymorphisms have been examined with breast cancer risk [20][21][22][23] as well as with other conditions that have been linked to estrogen [19,24,25] with mixed results.…”
Section: Introductionmentioning
confidence: 99%